An analytical model to estimate AVS/RS energy consumption. Issue 13 (2019) - D'Antonio, Gianluca; Bruno, Giulia; Traini, Emiliano; Lombardi, Franco
Abstract: Automation systems to support warehouse activities are a topic largely debated. Critical decisions on the technology to be adopted and the basic system attributes must be taken in the design phase; to support designers, several methodologies have been defined to evaluate performance indicators such as throughput, cycle time and equipment utilization. Conversely, smaller attention has been paid so far in the estimation of the energy necessary to perform the scheduled activities. Nonetheless, this topic is gaining popularity as the impact of renewable energy sources is increasing and the adoption of complex energy grids is gaining popularity. This paper is aimed at proposing an analytical model to evaluate the energy consumption of Autonomous Vehicle Storage and Retrieval Systems (AVS/RS), which exhibit higher flexibility and lower energy consumption compared to the traditional AS/RS. The proposed model is able to estimate the average energy consumption by accounting for realistic criteria adopted to store and retrieve unit loads. The proposed approach is validated by comparing the analytical estimation to the output of a simulation model.